Genome-wide prediction of G4 DNA as regulatory motifs: Role in Escherichia coli global regulation - Rawal, Pooja; Kummarasetti, Veera Bhadra Rao; Ravindran, Jinoy; Kumar, Nirmal; Halder, Kangkan; Sharma, Rakesh; Mukerji, Mitali; Das, Swapan Kumar; Chowdhury, Shantanu (Genome Research, 2006)
The role of nonlinear DNA in replication, recombination, and transcription has become evident in recent years. Although several studies have predicted and characterized regulatory elements at the sequence level, very few have investigated DNA structure as regulatory motifs. Here, using G-quadruplex or G4 DNA motifs as a model, we have researched the role of DNA structure in transcription on a genome-wide scale. Analyses of >61,000 open reading frames (ORFs) across 18 prokaryotes show enrichment of G4 motifs in regulatory regions and indicate its predominance within promoters of genes pertaining to transcription, secondary metabolite biosynthesis, and signal transduction. Based on this, we predict that G4 DNA may present regulatory signals. This is supported by conserved G4 motifs in promoters of orthologous genes across phylogenetically distant organisms. We hypothesized a regulatory role of G4 DNA during supercoiling stress, when duplex destabilization may result in G4 formation. This is in line with our observations from target site analysis for 55 DNA-binding proteins in Escherichia coli, which reveals significant (P < 0.001) association of G4 motifs with target sites of global regulators FIS and Lrp and the sigma factor RpoD (σ70). These factors together control >1000 genes in the early growth phase and are believed to be induced by supercoiled DNA. We also predict G4 motif-induced supercoiling sensitivity for >30 operons in E. coli, and our findings implicate G4 DNA in DNA-topology-mediated global gene regulation in E. coli.